AN ANALYSIS OF IDIOMATIC EXPRESSIONS USED BY CONTENT CREATORS ON TIKTOK - Diantri Nurjati Isworo Diantri; Prabowo Kusumo; Maria Yosephin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study covered the idiomatic expressions used by TikTok content creators. Finding out the meaning, characteristic, and contributions of idiomatic expressions for English teaching are the goals of this study. In 12 videos, the researcher discovered 54 idioms, which the writer has examined. The methodology for this study was qualitative research. The study's data sources were the idiomatic terms used in the content that TikTok content creators addressed. The study's nonhuman instrument is a smartphone, and the researcher is its human subject. Data categorization, selection, and reading comprised the study's three steps. This study searched for type idioms using Adam Makkai's idea. Idioms can be classified as either lexemic or sememic. All of the data was lexemic. Phrasal verb idioms, tournure idioms, irreversible binomial idioms, phrasal compound idioms, and integrating verb idioms are the five different characteristic of type lexemic idioms. The Adam Makkai theory is applied in this investigation. The researchers discovered 3 incorporating verb idioms, 26 phrasal compound idioms, 4 irreversible binomial idioms, 19 tournure idioms and 2 phrasal verb idioms.